The value of the calcium binding protein S100 in the management of patients with traumatic brain injury - Schiavi, P.; Iaccarino, C.; Servadei, F. (Acta Biomedica Atenei Parmensis, 2012)
Background: From the first study in 1995 the role of calcium-binding protein S100B in Traumatic Brain Injury (TBI) has been variously investigated in many clinical works. The aim of this work is to analyze the recent published reports with a reference to serum and CSF levels and to identify a possible role of S100 in the management of TBI. Methods: A MEDLINE search with a various number of query related to “S100” and “TBI” was performed from 2000 to 2011. All identified articles and abstracts have been reviewed Results: Serum and CSF samples of the marker well correlate in most of the papers to the degree of intracranial injury as determined by CT scans. Furthermore patients with the higher levels of S100B show a worse prognosis. In the paediatric age a relationship with the outcomes in spite of difficulties to determine normal values is also observed. Some proposal about a clinical use of S100B to decrease the number of neuroradiological examinations are present. Conclusions: S100B shows some interesting potentialities, but we have not enough evidence to insert this marker of brain damage in the protocols for management of TBI. However its use in experts’ hands in association with others clinical and radiological features may help to improve medical practice in the treatment of TBI.